2017
DOI: 10.1038/s41598-017-00522-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of microRNA expression profiles of Kashin-Beck disease, osteoarthritis and rheumatoid arthritis

Abstract: Kashin-Beck disease (KBD) is a chronic osteochondropathy with unclear pathogeny. In this study, we compared the microRNA expression profiles of 16 KBD patients, 16 osteoarthritis (OA) patients and 16 rheumatoid arthritis (RA) patients and 16 healthy controls in their blood specimens. miRNAs expression profiling was performed using Exiqon miRCURY LNATM miRNAs Array. miRNAs target genes were predicted using miRror suite. Another independent mRNA expression profile dataset of 20 KBD patients and 15 healthy contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…In human studies, Wu and colleagues examined the miRNA expression profiles of cartilage samples from OA, RA, and Kashin-Beck disease 28 . They found 18 differentially expressed miRNAs which were shared between KBD and OA vs. RA patients, including several with previous links to OA.…”
Section: Epigenetics: Noncoding Rnasmentioning
confidence: 99%
“…In human studies, Wu and colleagues examined the miRNA expression profiles of cartilage samples from OA, RA, and Kashin-Beck disease 28 . They found 18 differentially expressed miRNAs which were shared between KBD and OA vs. RA patients, including several with previous links to OA.…”
Section: Epigenetics: Noncoding Rnasmentioning
confidence: 99%
“…Meanwhile, adult KBD patients typically have advanced KBD, often accompanied by OA 4,6 . Recent studies have found differences in various cellular pathways between KBD and OA chondrocytes 5,7,8 , suggesting differences in multiple processes, such as metabolism, apoptosis, adaptive immune defence, cytoskeleton, cell movement and extracellular matrix turnover 4,[9][10][11][12] . However, these studies do not take into consideration the heterogeneity of articular cartilage cell types and therefore may be missing important information on cartilage degeneration processes specific to KBD or OA.…”
Section: Introductionmentioning
confidence: 99%
“…Epigenetics enables tight control of gene expression at the transcriptional level, resulting in changes in chromatin 3D structure, and at the translational level (microRNAs (miRNAs), long noncoding RNAs (lncRNAs), mRNA editing and mRNA stability) affecting protein expression [18]. The deregulation and dysfunction of mRNAs [19][20][21][22], lncRNAs [23,24] and miRNAs [25][26][27][28] in OA have been reported. Previously, Fu et al [23] revealed that a total of 710 mRNAs were differentially expressed in OA tissues.…”
Section: Introductionmentioning
confidence: 99%